Peran Interpersonal Pemimpin dalam Pengembangan Agribisnis Buah Naga - Delah Samanta Putri; Sri Subekti (Universitas Sebelas Maret, 2025)
The leaders have an important role in the development of Dragon Fruit agribusiness in the Pucangsari Farmers Group in Jambewangi Village, Sempu Sub-district, Banyuwangi Regency. The study aims to analyze the interpersonal role of the leader of the Pucangsari Farmers Group. The study used a qualitative descriptive method. Data collection was carried out through in-depth interviews, observation, and documentation. Research informants were selected as many as 16 people consisting of the group leader, 1 group administrator and 14 group members. The analysis used was the Miles and Huberman interactive analysis model. The results of the study showed that the role of the farmer group leader in the development of dragon fruit agribusiness consists of the role of responsibility, motivation, direction, and the role as a liaison. The role of the group leader’s responsibility to group members is to hold regular meetings, lead meeting events, gather group members, facilitate activity locations, receive assistance with processing tools, cooperate with fruit shops and supermarkets, and represent the group in meetings with the Department of Agriculture. The role of the leader is to motivate group members to make organic fertilizers and botanical pesticides, farm organically, process dragon fruit, and expand the target market. The role of the group leader is to direct group members to use organic fertilizers and homemade botanical pesticides and to farm better and correctly. The group leader also acts as a liaison during training, socialization, and marketing activities.